ECTHR_COMMITTEE 66438/09 vom 2. April 2015 , AFFAIRE PALAIOGIANNIS c. GRÈCE - Ecthr Committee (2015)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure pénale;Article 6-1 - Délai raisonnable); Violation: 6;6-1